Fatal occupational electrocutions in the United States. Issue 4 (1st December 2002) - Taylor, A J; McGwin, G; Valent, F; Rue, L W
Abstract : Introduction: The highest proportions of fatal occupational electrocutions have occurred among those employed in the electrical trades and in the construction and manufacturing industries. Methods: Data from 1992 through 1999 were obtained from the Bureau of Labor Statistics Census of Fatal Occupational Injuries. Results: Occupational electrocution deaths occurred almost entirely among males, with the highest rates among those aged 20–34 and among whites and American Indians. They were highest during the summer months, in the South, and in establishments employing 10 or fewer workers. The highest rates occurred in the construction, mining, and agriculture, forestry, and fishing industries and among trades associated with these industries. Conclusions: Electrocution continues to be a significant cause of occupational death. Workers need to be provided with safety training and employers, particularly smaller employers, persuaded of the need for safety training.